(untitled) (Nepal Journal of Environmental Science, 2013)
The grasslands of Nepal’s Terai are extremely rich in bird species with several globally threatened species. These birds are often quite sensitive to changes in the habitat quality and microclimate around them making them ideal indicators of the grassland ecosystem health. Unfortunately, very little is known about the grassland avifauna. This study was conducted to determine the avifaunal composition and diversity with respect to the vegetation height and patch openness in the grasslands of Shuklaphanta Wildlife Reserve by using open width line transect method along fire-lines. The birds and the vegetation were recorded using BBIRD protocol and the species diversity was calculated. The Kruskal-Walli test for differences in median populations and Canonical Correspondence Analysis (CCA) were also conducted. This study recorded 104 species birds belonging to 39 families among which 29 species were insectivorous, 17 herbivorous, 17 carnivorous and the rest omnivorous with 94 resident species and 10 summer visitor species. Covered patches of short grassland had highest number of species while covered patches of tall grasslands had the highest species diversity. The results from KruskallWallis test and CCA highlighted the need for the maintenance of ecological integrity of all the grassland habitat areas.